URGENSI SISTEM HUKUM BERBASIS LEGAL COMMUNITY EMPOWERMENT DALAM UPAYA MEMINIMALISASI KORBAN PERDAGANGAN UNTUK TUJUAN SEKSUAL TERHADAP PEREMPUAN DI INDONESIA - Hansel Kalama Ng; Hery Firmansyah Firmansyah (Faculty of Law - Tarumanagara University, 2017)
Along with the development of this era due to the tecnological advances, it grows the variety types of criminal modus operandi including the trafficking of women for sexual purposes. The rise of trafficking of women for sexual purposes was recorded at 1.359 cases since 1998-2010, it shown that Indonesia is vulnerable to this issue. The amount mentioned above only shows the cases which has exposed, in fact there are a lot of unexposed cases relating to the hidden victims who do not want to report their cases. Therefore, the urgency to seek for solutions in order to minimizing this crime will be very needed. One of the efforts is by improving the legal system by emphasizing on Legal Empowerment Community concept. The purpose of this concept is empowering the community based on participatory theory to persuade them for participating together to minimizing this crime. Thus, the prevention and repression on the Trafficking of Womer for Sexual Purposes not only done by Government but the community as well. Keywords: Trafficking of Women for Sexual Purposes, Hidden Victims, Legal Empowerment Community